2012
DOI: 10.1002/pc.22295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber surface treatments on the properties of short sisal fiber/poly(lactic acid) biocomposites

Abstract: Sisal fiber (SF)‐reinforced poly(lactic acid) (PLA) biocomposites were prepared from biodegradable PLA and surface‐untreated or ‐treated short SF by melt mixing and subsequent compression molding. It is found that the surface treatments facilitate good adhesion between SFs and PLA matrix, which is consistent with the higher mechanical properties of the treated‐SF/PLA biocomposites. Moreover, the surface treatments have similar effects on the biodegradability and water absorption of the biocomposites with the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…It was found that the mechanical properties of the fibers as well as the composites were greatly influenced by the fiber surface treatment methods. Similar studies were carried out by Zou et al [88] for short sisal fiber reinforced PLA.…”
Section: Pla and Natural Fiberssupporting
confidence: 76%
“…It was found that the mechanical properties of the fibers as well as the composites were greatly influenced by the fiber surface treatment methods. Similar studies were carried out by Zou et al [88] for short sisal fiber reinforced PLA.…”
Section: Pla and Natural Fiberssupporting
confidence: 76%
“…Short coir fibers (250 g) were added to a 1 L mixed solution containing 160 mL (30%; w/w) of hydrogen peroxide and 0.5 g of sodium hydroxide at 85 ∘ C and magnetically stirred for 1 h. Subsequently, the soaked coir fibers were washed thoroughly with distilled water and dried in an oven at 60 ∘ C for 12 h [24,25]. The fibers were treated as treated coir fiber samples.…”
Section: Materials and Fibermentioning
confidence: 99%
“…As mentioned, some of the biodegradable polymers engineering properties in their neat form may not be satisfactory or equivalent to those offered by conventional polymers, thus limiting the performance in many cases . An opportunity to improve biodegradable resins is to reinforce them by vegetable fibers, as shown by several studies .…”
Section: Introductionmentioning
confidence: 99%